"As far as the government is a good government, it is democratic": Citizenship education in China. (December 2015) - Zhang, Xiudi
The concept of citizenship is mainly viewed as a Western construct. This article argues an understanding of citizenship education in China not only simply as a grounding in schooling and procedural knowledge of systems of Chinese government but, more broadly, whether in schools or society, whether in China or overseas, that develops dispositions, characters, and knowledge that reflect out who those Chinese young generation are? Democracy is a sensitive topic in China, and it can reflect a complex relationship between citizens and the government. This article, from the Chinese perspective, compares and contrasts the Chinese view of citizenship. It reveals a complex, sometimes contradictory relationship between the individual and state, which is deeply rooted in Chinese culture and context, and provide a critical reflection on Chinese citizens. In conclusion, this researcher calls for a greater commitment to, and a more nuanced understanding of, citizenship education in China.